Inflammatory F2-isoprostane, prostaglandin F2α, pentraxin 3 levels and breast cancer risk: The Swedish Mammography Cohort. (October 2016) - Basu, Samar; Harris, Holly; Wolk, Alicja; Rossary, Adrien; Caldefie-Chézet, Florence; Vasson, Marie-Paule; Larsson, Anders
Abstract: Introduction: Breast cancer is a common cancer among women. Identifying cellular participation of F2 -isoprostane, prostaglandin F2α (PGF2α ) and pentraxin 3 (PTX3) in cancer we evaluated whether their prediagnostic systemic levels that originate from different inflammatory pathways were associated with breast cancer risk. Methods: Seventy-eight breast cancer cases diagnosed after blood collection and 797 controls from the Swedish Mammography Cohort were analysed for urinary F2 -isoprostane, PGF2α and plasma PTX3 levels. Results: None of the biomarkers investigated were significantly associated with breast cancer risk. However, there was the suggestion of an inverse association with PTX3 with multivariable adjusted ORs (95% CI) of 0.56 (95% CI=0.29–1.06) and 0.67 (95% CI=0.35–1.28) for the second and third tertiles, respectively (ptrend =0.20). No associations were observed between F2 -isoprostane (OR=0.87; 95% CI=0.48–1.57; ptrend =0.67) and PGF2α metabolite (OR=1.03; 95% CI=0.56–1.88; ptrend =0.91) comparing the top to bottom tertiles. Conclusions: The systemic levels of F2 -isoprostane, PGF2α and PTX3 witnessed in women who later developed breast cancer may not provide prognostic information regarding tumor development in spite of their known involvement in situ cellular context. These observations may indicate that other mechanisms exist in controlling cellular formation of F2 -isoprostane, PGF2α and PTX3 and their systemic availability in breast cancer patients. Highlights: Breast cancer is a life-threatening and leading cause of cancer death among women. Recognizing cellular participation we hence examined if prediagnostic circulating levels of F2 -isoprostane, PGF2α and PTX3 were associated with breast cancer risk. Assessing systemic levels of these biomarkers early to define breast cancer risk is most relevant. None of these examined biomarkers were significantly associated with breast cancer risk. These findings reveal a new understanding on the role of systemic F2 -isoprostane, PGF2α and PTX3 in breast cancer which provide no prognostic information on tumor development in spite of their known involvement in situ cellular context.